Diversidade genética e padrões de suscetibilidade à deltametrina em populações de triatoma brasiliensis, Neiva, 1911 (hemiptera: reduviidae), no município de Jaguaruana, Ceará. - Silva, Luiz Osvaldo Rodrigues (2023)
The strategy for controlling Chagas disease basically consists of interrupting vector transmission by combating domestic triatomines through residual insecticide applications. This control strategy has been employed for over 40 years in Brazil, which may have selected various populations with altered resistance status. The aim of this study was to monitor the susceptibility profile of T. brasiliensis to the insecticide deltamethrin, characterize the genetic structure of these populations, and describe the social, cultural, and behavioral characteristics of residents that may be related to the persistence of vectors in the domestic environment. The study was conducted in four rural localities in the municipality of Jaguaruana, Ceará. A total of 144 Household Units (UDs) were sampled for the collection of triatomines (N=961) for bioassays and cross-sectional population study. The population used as a reference lineage for susceptibility in biological assays originated from Umari-CE. The characterization of the genetic structure of populations was developed through the study of microsatellites using the transposition technique. Social, cultural, and behavioral characteristics of the communities were collected through interviews using a semi-structured questionnaire. The bioassays described a LD50 ranging from 0.29 to 0.45 and resistance ratios (RR50) between 1.01 to 1.55, all being susceptible. The T. brasiliensis populations in the localities of Cipriano Lopes, Latadas, and Quixabinha showed significant differences in LD50 compared to the reference population (TbREF) when the confidence limits overlapped at the 95% level. Microsatellite studies revealed low genetic diversity. The average number of alleles observed per locus ranged from 1.89 (Tb860) to 5.13 (Tb7180), with an average of 3.19. The sample from João Duarte Silvestre (JDuaWild1) had the highest average number of alleles (NA=4.20) and allelic richness (RA=3.28), while the UD of 10c1 de Latada (Lat18c1) had the lowest average number of alleles (NA=2.00) and allelic richness (RA=1.78). Molecular variance analysis (AMOVA) demonstrated that 67.2% of the genetic variability is among all individuals, 22.6% among individuals from the same sample, and 10.2% among samples. Fixation indices showed p value ≤ 0.05, indicating inbreeding in the sample with the presence of subpopulations. The population-based cross-sectional study revealed that the predominant construction of the walls of UDs is masonry with plaster at 68.4%, with cracks found in 81.9% of the surveyed UDs, with higher percentages found in Latadas (90.7%) and Jenipapeiro (88.9%). The floor predominantly consists of cement at 79.5%, and the roof is 100% made of clay tiles. Regarding the use of domestic insecticides, 39.7% of residents use insecticides for insect control inside the home, and 48.2% use them in the peridomicile. Domestic animal breeding is common in the communities. In the peridomicile, there is a high diversity of annexes that can serve as shelters and breeding sites for T. brasiliensis, favoring the process of household reinfestation. In conclusion, the tested T. brasiliensis populations are susceptible to the insecticide deltamethrin, exhibit low gene flow, and have structured subpopulations. The characteristics of UDs, combined with the residents' habits, may contribute to the maintenance of triatomine populations close to dwellings.